Legal protection for victims of criminal acts of neglecting children with disabilities from the perspective of Maqashid Syariah - Sabrina Putri; Rizal Rizal; Muhamad Sadi (PT WIM Solusi Prima, 2026)
This study examines legal protection for victims of criminal abandonment of children with disabilities from the perspective of maqashid syariah. Children with disabilities face double vulnerability and require special protection from the state, family, and society. Based on data from the Ministry of Women Empowerment and Child Protection, 1,381 cases of child abandonment were recorded in Indonesia in 2024, while the WHO estimates around 240 million children with disabilities worldwide. This study employs a normative juridical method using statutory and conceptual approaches. The results show: first, forms of abandonment of disabled children include physical, educational, emotional, social, and health neglect; second, from the perspective of maqashid syariah, legal protection for victims of abandonment constitutes part of three primary objectives of Islamic law hifz al-nafs (protection of life), hifz al-aql (protection of intellect), and hifz al-nasl (protection of lineage). Optimal legal protection encompasses not only criminal sanctions against perpetrators but also rehabilitation, legal assistance, health services, inclusive education, and psychological recovery.